Performance of Bio Concrete by Using Bacillus Pasteurii Bacteria - Metwally, Gehad A. M.; Mahdy, Mohamed; Abd El-Raheem, Ahmed El-Raheem H. (Civil Engineering Journal, 2020)
In concrete, cracking is a common phenomenon due to its relatively low tensile strength‎ ‎, which occurs due to external loads and imposed deformations‎‎. The main research objective is to create a kind of self-healing concrete by employing mineral producing bacteria Bacillus pasteurii‎ to locate the rift in the most favourable circumstances for autogenous healing to take place. Self-healing concrete containing bacteria has been generated for this study through the application of bacterial self-healing elements as ‎spores ‎and nutrients with different percentages of bacteria ranging from (10% - 25%) as a replacement of mixing water is added at the time of pouring. The bacteria influence was observed by Scanning Electron Microscope (SEM) and with Energy ‎Dispersive X-ray Spectrometer. The mechanical properties and durability of a thirty-five mixture were ‎examined. The optimal blending content proportion was ‎10SF20BC, which showed an increment in compressive strength and flexural strength compared to the control mixture ‎to ‎reach 79.16%, 50% respectively and 24.38% enhancement in sulfate resistance. The highest percentage of calcium carbonate precipitations was ‎9.49% of a weight of ‎mixtures ‎elements, which, in turn, revealed the highest area repair rate, which was able to fill the ‎crack with widths leads to 0.80 mm.